Caracterização demográfica de Phrynops hilarii (Testudines, Chelidae) em um ambiente urbano de Porto Alegre, RS, Brasil - Peres, Lísia Cristina Naud (Universidade do Vale do Rio dos Sinos, 2010)
In this study is presented the first population parameters to the population of Phrynops hilarii from “Lago dos Pedalinhos” (30º02'13"S; 51º13'03"W), an urban lake from the city of Porto Alegre – Brazil. The population structure, size, abundance, and sex ratio as well sexual dimorphism in size were analyzed. The captures and data collection were conduced weekly, between May and December 2009. All the captured specimens were weighed, sexed (whenever possible) and marked with a number of identification. In order to evaluate the differences in size between sexes nine body measurements were taken from adult males and females. After completed the procedure, all individuals captured were released in the same place that they were caught. The population abundance was estimated by Jolly-Seber method for open populations and the sex ratio was calculated by the division between the total number of males and females. The sexual dimorphism in body measurements were tested between sexes using t-test, just for adult individuals with known sex. As a result, 53 specimens of P. hilarii were captured, which 77% were adults and 22% subadults. From this total, 16 were males, 25 females and 12 were of unknown sex. The population abundance of P. hilarii in the study area was estimated in 282.67 specimens. The sex ratio was statistically different from the expected ratio 1:1 and was biased in favor of females (1 male to 1.56 females). The t-test results revealed pronounced sexual dimorphism in body size, with females being larger than males, with the exception of the tail’s measurements (CCD1 and CCD2). In chelonians the sexual dimorphism in size is common and it may be one of the factors that influence the maturation and differential growth between the sexes. It is believed that studied population is formed, mainly, by animals released by the local co mmunity, after being kept in captivity, like pets. The observed results suggest that the ch elonian populations that live in urban parks are able to keep the regular population parameters similar to the wild populations of the species, even living in highly impacted areas. In addition, it indicates that this population is extremely resistant to anthropogenic pressure. The mortality of chelonians in urban parks generally is due to direct human actions, such as maltreatment, running over, predation and by the attack of domestic animals, as well pollution and competition with related species that live in the same area (Trachemys dorbigni and T. scripta elegans). Finally, the study of chelonians from urban parks could be used as a model for under standing the real effects of the human activity on the wild populations of freshwater turtles
Keywords: Abundância populacional; Dimorfismo sexual; Estrutura populacional; Phrynops hilarii; Quelônios urbanos; Razão sexual; Testudines; Population abundance; Population structure; Sex ratio; Sexual dimorphism; Urban turtles; ACCNPQ::Ciências Biológicas::Biologia Geral